1991
DOI: 10.1017/s0022029900029745
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cations and anions on the rate of the acidic coagulation of casein micelles: the possible roles of different forces

Abstract: Raw skim milk was diluted 1000-fold using distilled water or various salt solutions as specified. Smooth, hyperbolic profiles of coagulation rate v. pH for casein were calculated from recordings of turbidity (400 nm) with time. The effects of pH, cation type, anion type and cleavage of/c-casein by chymosin (EC 3.4.23.4) were determined. The maximum of pH-coagulation rate profiles decreased by 63, 85 and 94 % when the skim milk diluent was changed from water to salt solutions of NaCl (100 mM), CaCl 2 (50 mM) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…This would will lead to different ratios of casein-bound inorganic ions. Bringe and Kinsella (1991) suggested that inorganic ions in general can affect the protein-protein interactions between casein micelles during acid gel formation by altering the repulsive hydration forces between protein surfaces. They also showed that Ca 2+ ions had a greater tendency to inhibit coagulation of casein than Na + ions.…”
Section: Discussionmentioning
confidence: 99%
“…This would will lead to different ratios of casein-bound inorganic ions. Bringe and Kinsella (1991) suggested that inorganic ions in general can affect the protein-protein interactions between casein micelles during acid gel formation by altering the repulsive hydration forces between protein surfaces. They also showed that Ca 2+ ions had a greater tendency to inhibit coagulation of casein than Na + ions.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of pH on micelle structure was well known and acidification mechanisms appears to be more complex than a simple discharge of casein micelles. Nevertheless, one of the main effects of lowering the pH of milk is diminution of the micellar net negative charge [57][58][59]. By applying the mass action law (pH = pK + log[R-COO − ]/[R-COOH]), it would be possible to evaluate the R-COO − number due to carboxyl groups (acidic sugar N -acetylneuraminic acid, aspartic acid, glutamic acid) as related to pH value (Table 3).…”
Section: Interfacial Behavior Of Acidified Whole-milk Proteinsmentioning
confidence: 99%
“…To describe the effects of calcium addition to milk, numerous physicochemical studies have been carried out [3,4,7,8,10,11,14,15,21,23,24,26,27,31,34,35,37,39]. These studies principally showed that addition of calcium to milk resulted in a new distribution of ions between milk serum and casein micelles, leading to physicochemical changes in casein micelles.…”
Section: Introductionmentioning
confidence: 99%